Empowering Rural Entrepreneurs through Independent-Entrepreneurship Literacy Program - Prasandha, Diyamon; Susanti, Yuni Dwi (UI Scholars Hub, 2022)
It is well known that the economic development of a country largely depends on the economic development and the living standards in rural areas. Yet, it is also a fact on the contrary that there is a major problem faced by rural entrepreneurs, namely illiteracy. Illiteracy causes some other problems, including lack of financial resources, low business management skills, lack of proper marketing, and lack of human resource management. The same situation is encountered by bamboo craftsmen in Rogomulyo Village, who has low entrepreneurial competencies. This condition encourages the need for entrepreneurship education in a rural area. By integrating the concept of community empowerment and entrepreneurship capacity building, the present program implemented independent-entrepreneurship literacy for bamboo craftsmen in Rogomulyo Village. It aims to enhance their competencies in running a small business. For reaching that outcome, this program applied Participatory Action Research (PAR) which consists of five stages, including problem identification, action planning, acting, evaluation, and specifying learning achieved. More specifically, the entrepreneurship programs implemented are business literacy, financial literacy, and digital marketing literacy. The finding suggests that the implementation of an independent-entrepreneurship literacy program could enhance bamboo craftsmen’s competencies so that they could develop their bamboo craft business in Rogomulyo Village. However, they still require support from several parties, including local government, local companies, and others.